(untitled) (Swiss Medical Weekly, 2019)
Ocular inflammations such as uveitis and scleritis can lead to significant visual impairment if not treated properly. To limit potentially sight-threatening complications, good control of the inflammation in the acute phase is necessary. Corticosteroids have been the mainstay of ocular therapies for many years, but high doses of corticosteroids, which are required to maintain quiescence in severe uveitis, can be associated with many systemic and ocular complications. In order to limit steroid side-effects, classic immunosuppressant and immunobiologic agents have been widely used as steroid-sparing agents. In this review, we summarise the immunosuppressive drug therapy utilised in the treatment of ocular inflammatory diseases.